Estoppel And Substantive Legitimate Expectation: Parallel Doctrines In Public Law? - C.K.G. Pillay, Sudha d/o (Journal of Malaysian and Comparative Law, 1999)
Estoppel is premised on the notion that justice prevails over truth. Thus, a person who makes some statement or representation which induces another to act to his detriment in reliance on the truth of the statement or representation, is not allowed to later deny the truth of it, notwithstanding that the same may have been wrong.